2020
DOI: 10.1128/msphere.00817-20
|View full text |Cite
|
Sign up to set email alerts
|

The Major Chromosome Condensation Factors Smc, HBsu, and Gyrase in Bacillus subtilis Operate via Strikingly Different Patterns of Motion

Abstract: Although DNA-compacting proteins have been extensively characterized in vitro, knowledge of their DNA binding dynamics in vivo is greatly lacking. We have employed single-molecule tracking to characterize the motion of the three major chromosome compaction factors in Bacillus subtilis, Smc (structural maintenance of chromosomes) proteins, topoisomerase DNA gyrase, and histone-like protein HBsu. We show that these three proteins display strikingly different patterns of interaction with DNA; while Smc displays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Note that the values of these coefficients are about three-fold larger than in the untreated case, indicating larger local mobility of chromosomal segments. These results are consistent with previous evidence showing that rifampicin effects reduces the static fraction of SMC proteins in B. subtilis and increases its diffusion ( 71 ).…”
Section: Discussionsupporting
confidence: 93%
“…Note that the values of these coefficients are about three-fold larger than in the untreated case, indicating larger local mobility of chromosomal segments. These results are consistent with previous evidence showing that rifampicin effects reduces the static fraction of SMC proteins in B. subtilis and increases its diffusion ( 71 ).…”
Section: Discussionsupporting
confidence: 93%
“…In relation, proteins diffusing through the chromosome by sliding from one DNA strand to the next via nonspecific DNA binding have been reported with diffusion constants in the range of that of the medium-mobile LytF fraction ( Rösch et al. , 2018a ; Schibany et al. , 2020 ; Wisniewska et al.…”
Section: Resultsmentioning
confidence: 99%
“…The other candidate, LrpC, is a medium‐abundance homo‐octameric protein whose concentration increases ~threefold at the early stationary phase when compared to exponentially growing cells (García‐Tirado, 2011). Cytological studies revealed that the pattern of localization of GFP‐LrpC in exponentially growing cells is similar to that of SMC‐GFP (Britton et al ., 1998); García‐Tirado, 2011; Schibany et al ., 2020). In the absence of LrpC, the DAPI‐stained nucleoid increases in volume (García‐Tirado, 2011).…”
Section: Resultsmentioning
confidence: 99%